(untitled) (Revista de Medicina Clinica, 2025)
Background: Plasmacytoma is a monoclonal proliferation of plasma cells that accounts for 3-5% of all plasma cell malignancies, with a male predilection and a high progression to multiple myeloma. We present the case of a 46-year-old female patient who was evaluated in the emergency department of UPAEP Hospital, Christus Muguerza, Puebla, for a fracture of the left proximal femur not associated with trauma. Imaging studies, fracture stabilization surgery, and a biopsy were performed. Histopathology and immunohistochemistry revealed a malignant neoplasm with a plasmacytoid appearance that was positive for CD-138, MUM-1, and kappa and lambda light chains. Case report: The patient’s clinical notes, imaging studies, laboratory results, biopsy and immunohistochemistry were collected and analyzed. Discussion: We present the case of a 46-year-old female patient who presented with a pathologically determined fracture of the left proximal femur. A specific approach was used for the fracture, and extensive imaging, biopsy, and laboratory studies were performed, concluding with a malignant neoplasm with a plasmacytoid appearance that was positive for CD-138, MUM-1, and kappa and lambda light chains.